Automated network management systems : current and future capabilities - Comer, Douglas (Upper Saddle River, NJ : Pearson Prentice Hall, 2007)
Now more than ever, there is a big opportunity for research leading to automated systems that manage networks. In this innovative new book, Comer examines possibilities for the future, including ways to build software that automates management tasks. KEY TOPICS: Describes existing tools, technologies, platforms, and paradigms for network management. Covers the basics and define the scope of the problem. Aims to define terminology, but refers to standard network technologies and protocols (e.g. Ethernet, DSL/cable modem, TCP, IP, DHCP, and DNS) without giving details. Assumes a basic understanding of networking. A comprehensive guide for programmers or other information technology professionals who want to increase their network management skills.
Basics And Definitions -- Introduction- Present NM as the least-understood aspect of networking -- A Review Of Network Elements- Give example systems and configurable parameters in each -- The Network Management Problem- Explain scale and complexity -- Define carrier, provider,enterprise, edge, access, core, and FCAPS model -- Note: next chapters expand FCAPS and give examples -- Configuration And Operation- Expand definition and give examples -- Fault Detection And Correction- Expands definition and gives examples -- Measurement And Accounting- Expands definition and gives examples -- Performance Monitoring And Assessment- Expands definition and gives examples -- Security- Expands definition and gives examples -- Existing Tools And Platforms For Network Management -- Management Tools And Technologies- Overview of everything from ping through integratedapplications, including OpenView, CiscoWorks, and opensource tools -- Simple Network Management Protocol (SNMP)- Explain paradigm, functionality, and limitations -- Flow Data And Flow Analysis (NetFlow)- What is it, how data is captured, what the packetscontain, and what can be learned -- NetFlow as an example -- Routing And Traffic Engineering- Technologies for setting paths -- Fast failover -- BGPissues -- Management Scripting- Motivation -- Stand-alone scripts (expect), andscripting interfaces for applications such as servers -- Examples of scripts from Cisco's CNR productand examples of stand-alone scripts -- Moving Forward: The Future Of Network Management -- Next-Generation Network Management- The question of whether network management can beautomated, the conditions under which automation ispossible -- A list of desiderata for management automation -- Characteristics -- Give examples of complex situations tomanage -- Architectures For Network Management Software-Discussion of architectures and possible approaches -- Emphasize the need for new abstractions -- Generic framework into which modules can be inserted;software backplane -- Tiered hierarchy -- Database-centric -- External expectation verifier -- Representation, Semantics, And Information Models - Representation of information -- Syntactic andsemantic specification -- Information modeling andmodel-driven design -- UML -- Standard models such asCIM and MTNM -- Complexity of models and consequences -- Design Tradeoffs-Engineering tradeoffs and costs -- Summary Of Open Questions And Research Problems -- Table of Contents provided by Publisher. All Rights Reserved.
Includes bibliographical references (p. [331]-333) and index.
1
Keywords: Computer networks -- Management; Computer networks -- Management -- Automation